Off-line and on-line optical monitoring of microalgal growth - Lazcano-Hernández,Hugo-Enrique; Aguilar,Gabriela; Dzul-Cetz,Gabriela Antonia; Patiño,Rodrigo; Arellano-Verdejo,Javier (PeerJ, 2019)
The growth of Chlamydomonas reinhardtii microalgae cultures was successfully monitored, using classic off-line optical techniques (optical density and fluorescence) and on-line analysis of digital images. In this study, we found that the chlorophyll fluorescence ratio F685/F740 has a linear correlation with the logarithmic concentration of microalgae. By using digital images, the biomass concentration correlated with the luminosity of the images through an exponential equation and the length of penetration of a super luminescent blue beam (λ = 440 nm) through an inversely proportional function. The outcomes of this study are useful to monitor both research and industrial microalgae cultures.
Keywords: Chlamydomonas reinhardtii; Chlorophyll fluorescence; Chlorophyll optical density; Fluorescence ratio; Chl a fluorescence images; C. reinhardtii cultures growth; Proximal remote sensing